The Polarization of Employment in German Local Labor Markets - Hanna Wielandt; Charlotte Senftleben (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
This paper uses the task-based view of technological change to study employment and wage polarization at the level of local labor markets in Germany between 1979 and 2007. In order to directly relate technological change to subsequent employment trends, we exploit variation in the regional task structure which reflects a region s potential of being affected by computerization. We build a measure of regional routine intensity to test whether there has been a reallocation from routine towards non-routine labor conditional on a region s initial computerization potential. We find that routine intensive regions have witnessed a differential reallocation towards non-routine employment and an increase in low- and medium-skilled service occupations. Our results corroborate the predictions of the task-based framework and confirm previous evidence on employment polarization in Germany in the sense that employment growth deteriorates at the middle of the skill distribution relative to the lower and the upper tail of the distribution.
Keywords: R23; J24; J62; 330